“Hand in hand, never elbow”: Women leaders in the municipal union of Bariloche, Argentina (1983-2011) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
The history of women in unions has been silenced despite the fact that they have always been present in workers’ organizations. This is due to the logic that shaped the beginnings and consolidation of unionism throughout the world. In this article, we present the reconstruction of the life story of María Severino and Graciela Bedini, two women leaders of the Union of Workers and Municipal Employees of the city of San Carlos de Bariloche. We will explain the particularity of their promotions to the power in the union structure, to the heat of the legislation and the new spaces created to encourage the participation of women in labor orga-nizations and their demands, since the return of democracy in Argentina in 1983. We are interested in analyzing to what extent these feminine leaderships were an exception and to what extent that institution has reproduced gender asymmetric power relations and the male model that prevails in the majority of unions. In addition, it is a contribution to the history of workers from a local and regional perspective.
Keywords: Unionism; Women leaders; work relationships; world of work; life stories